(untitled) (Journal of the Association for the Study of Australian Literature, 2013)
This article surveys the short fiction jointly produced by Beatrice Osborne and Hilary Lofting under the names Margaret Fane and Hilary Lofting between 1919 and 1929, in which they create distinctive territories (the western periphery of Sydney, and the contrasting wealthy suburbs around Elizabeth Bay, Double Bay, Potts Point and residential Macquarie Street, and the poorer suburb of Woolloomooloo). The stories foreground a middle way between self-sufficiency and wealth; the natural life is preferred to the artifice and extremes of city life, and all the stories argue for individualism and independence of spirit, characterised by pursuit of an active life, appreciation of beauty, and following one’s will rather than conforming to social expectation.